The Copenhagen adduction exercise: awareness, implementation and opinion of worldwide professional and semi-professional soccer players and coaches - Al Attar, W. S. A.; Qasem, A.; Al Masoudi, N. S.; Ghulam, H. S. H.; Sanders, R. H. (British Journal of Sports Medicine, 2021)
Background: Groin injuries are frequent injury commonly seen in any sport contain sudden changes in direction, rapid acceleration and deceleration, and kicking which are all available in soccer. The Copenhagen adduction exercise increases the eccentric hip adduction strength leads to reduce the incident of groin injury. Objective: To assess the professional and semi-professional soccer players and coaches' awareness, implementation, and opinion of the Copenhagen adduction exercise. Design: A cross-sectional study. Setting: An online survey for all continental football federations. Patients (or Participants): A total of 1621 male and female professional and semi-professional soccer players and coaches completed the survey. Interventions (or Assessment of Risk Factors): The questionnaire consisted of questions covering the awareness, implementation, and professional and semi-professional soccer players and coaches' opinion of the Copenhagen adduction exercise. Main Outcome Measurements: The primary outcomes were awareness level, implementation rate, and opinion of the effectiveness of the Copenhagen adduction exercise in reducing groin injury. Results: A total of 584 (36%) of professional and semi-professional soccer players and coaches were aware of the Copenhagen adduction exercise, 487 (30%) were implementing the Copenhagen adduction exercise in their current practice. Participants who implemented the Copenhagen adduction exercise reported a positive perception about the program efficacy, with a score of 8±1.10) out of 10. Conclusions: Further work needs to be done to educate soccer players and coaches about the importance of implementing the Copenhagen adduction exercise and its effectiveness in reducing groin injury to enhance the Copenhagen adduction exercise' implementation.